Death of fetal surveillance: main causes of study - América Maria Eleutério Dell Menezzi; Isabella Drumond Figueiredo; Estefânia Wanderley Barbosa Lima; Júlio César de Almeida; Fúlvia Karine Santos Marques Santos Marques; Camila Ferreira de Oliveira; Nair Amélia Prates Barreto; Lucinéia de Pinho (O Mundo da Saúde, 2016)
The stillbirth is a major cause of perinatal mortality, and understanding its causes is essential to improve prenatal care provided to pregnant women. In this sense, the study characterized the cases of antepartum intrauterine fetal death recorded in a maternity ward in the North of Minas Gerais between January 2010 and December 2012. Medical records obtained were evaluated by the Child Mortality Committee of Motherhood. They were included in the sample 26 records of pregnant women with fetal death diagnosis occurred before the onset of labor, gestational age less than 20 weeks and birth weight or greater than 500g. Data were collected using a structured questionnaire and evaluated by descriptive statistics. Most of the women were between 18 and 29 years and had a pregnancy to term. It was observed that 69% of cases of death had no associated risk factor, which is a higher rate to those presented in the medical literature. In cases with identifiable causes, attributed to 7.7% of cases the specific hypertensive disorders of pregnancy, 3.8% diabetes mellitus, 3.8% to urinary tract infection, 3.8% to 11.5 and polyhydramnios 11,5% multiple complications. The high frequency of deaths without risk factors indicates that poor quality of information on perinatal death, especially fetal death.